2009
DOI: 10.1111/j.1742-481x.2009.00635.x
|View full text |Cite
|
Sign up to set email alerts
|

Topical silver‐impregnated dressings and the importance of the dressing technology

Abstract: A wide variety of silver-impregnated wound dressings has become available in recent years. This has given the practitioner choice but little evidence by which an appropriate dressing may be selected. In many instances, the ancillary function(s) of the dressing will become differentiating factors that influence choice. For example, the dressing capacity to manage exudate, maintain an optimum moist environment, reduce or avoid maceration, maintain an intimate contact with the wound bed, promote autolytic debride… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…Silver, with its antimicrobial properties, reduces the bioburden and associated endotoxins in wounds. It also has the ability to directly sequester endotoxins with a net effect of promoting re-epithelialization and improving healing [61]. Excess levels of matrix metalloproteinases are also associated with delayed healing, and cause increased inflammation.…”
Section: Discussionmentioning
confidence: 98%
“…Silver, with its antimicrobial properties, reduces the bioburden and associated endotoxins in wounds. It also has the ability to directly sequester endotoxins with a net effect of promoting re-epithelialization and improving healing [61]. Excess levels of matrix metalloproteinases are also associated with delayed healing, and cause increased inflammation.…”
Section: Discussionmentioning
confidence: 98%
“…These products are numerous and have been reviewed elsewhere [25,[36][37][38]. Nanocrystalline silver releases small particles of silver over a long period of time, increasing the wound surface area in contact with the silver particles and the duration of that contact [38,39].…”
Section: Topical Application For Burnsmentioning
confidence: 99%
“…The results of these studies differ widely, and a recurring theme in the relevant meta-analyses is the need for more rigorous trials before any conclusive statements can be made [54][55][56][57][58]. Because of the countless products available for the management of chronic wounds, both with and without silver, an in-depth review of each is beyond the scope of this review but can be found elsewhere [25,36,37]. The variety of products and the heterogeneity of studies evaluating them provide insufficient evidence that silver dressings are consistently superior to non-silver dressings for the treatment of chronic or infected ulcers, but there is some evidence supporting the use of silver-containing products for shortterm wound care in specific patient populations.…”
Section: Topical Application For Ulcersmentioning
confidence: 99%
“…A recent publication 7 suggested that viewing silver dressings as passive delivery vehicles/carriers for silver may disregard contributions of the carrier dressing. A broader perspective considers the influence of the carrier dressing on wound progression by managing factors important to wound healing, including exudate management, conformability to the wound bed, and bacterial sequestration.…”
Section: Peer-reviewed Datamentioning
confidence: 99%